RESPONS PEMBACA PEREMPUAN TERHADAP TOKOH PEREMPUAN DALAM TEKS NOVEL “DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN” KARYA TERE LIYE - Marti Marganingsih; Ade Husnul Mawadah; Firman Hadiansyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
Literary reception is text processing in giving meaning to a literary work. The emergence of literary works becomes meaningful and valuable through the enrichment of various reviews and reader understanding. Readers' reviews of literary works can be observed from several things, including through reader responses. Analysis of the reader's response plays an essential role in measuring the reader's understanding of a literary work. The purpose of this study was to determine the reader's response to the female character in the novel. The object identified is the novel “Fall Leaves Never Hates the Wind” by Tere Liye. This study uses descriptive analysis method by relying on data in the form of respondents' responses to the novel. The data in this study are the reader's answers contained in the questionnaire. The source of the data for this research is a question questionnaire via google form. This study uses two research techniques, namely [1] listening and note-taking techniques and [2] collecting reader answers using google form. Data analysis is done by interpreting the data according to the theory used. The responses included (1) Tania as the most liked character (94.9%) (2) Tania is a tough woman and should be followed by an example (98.6%) (3) Tania fights for her family life (100%) (4) Readers agree with Tania's attitude that busking to lighten the burden on the family (84.7)% (5) Readers agree if women avoid work as buskers (57.6%) (6) Readers agree if a daughter works to help her mother (100%) ( 7) The reader agrees if Tania continues her studies in Singapore (100%) (8) The reader agrees if Tania expresses her love for Om Danar (59.3%) (9) The reader chooses that Tania remains kind to Kak Ratna (98.3% ) (10) Readers agree that Tania strengthens herself and hopes to see a better tomorrow (100%). Keywords: female reader response; female characters; the text of the novel The Falling Leaves Never Hated the Wind